2017
DOI: 10.1016/j.jvs.2016.12.145
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of thoracic endovascular repair for type B aortic dissection with multichanneled morphology

Abstract: MCAD was identified in a small but not insignificant number of our patients presenting with type B AD. Urgent or elective TEVAR was indicated in all our patients with MCAD. In patients with MCAD, full TL collapse was associated with worse outcomes, and this finding may indicate the need for more urgent or emergent repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Moreover, MCAD with TL full collapse was identified as a high-risk factor for hemodynamic instability. 5 As shown by the presented images and hemodynamic analysis using 4D flow MRI data, the complex spatial and temporal flow distribution of MCAD was confirmed in either the proximal or distal thoracic aorta. Quantifications of blood flow and velocities, especially in FLs, revealed significant variations throughout the cardiac cycle.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Moreover, MCAD with TL full collapse was identified as a high-risk factor for hemodynamic instability. 5 As shown by the presented images and hemodynamic analysis using 4D flow MRI data, the complex spatial and temporal flow distribution of MCAD was confirmed in either the proximal or distal thoracic aorta. Quantifications of blood flow and velocities, especially in FLs, revealed significant variations throughout the cardiac cycle.…”
Section: Discussionmentioning
confidence: 60%
“… 4 In fact, the natural course of MCAD is still unpredictable, especially for those with full true lumen (TL) collapse. 5 Regarding TEVAR for MCAD, limited literature is available on how the timing of intervention and treatment strategies may affect patient outcomes and potential complications. Previous studies suggested that the perioperative mortality and morbidity in patients with MCAD were much higher than in patients with DCAD.…”
mentioning
confidence: 99%
“…TEVAR for TBAD is an exciting topic and an area of widespread research and rapid publication. 20 The present prospectively maintained retrospective registry data do not answer all the possible questions about this topic. The registry lacks important data points regarding case planning, device delivery techniques, and perioperative lumbar drain management but does provide important insights.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have suggested that the aortic walls of MCAD patients are fragile, particularly in the subgroup of patients with Marfan syndrome. 2,3,11 The external wall is not strong enough to support the hemodynamic stress. MCAD, especially in patients with full TL collapse, seems to be an independent risk factor for hemodynamic instability or impending aortic rupture, so early surgical or endovascular intervention is recommended, 3,11,12 though the optimal treatment strategy has not been fully determined…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the morphology of double-channel aortic dissection, MCAD has significantly different and complex flow patterns and hemodynamics, which can lead to more complications after conventional primary tear repair. 2,3 Intravascular ultrasound (IVUS) can provide a real-time assessment of the aortic diameters and origins of the branches, offering valuable information for evaluating an aortic dissection, with precise localization of the relevant pathologies. 4 Herein we report the IVUS-assisted endovascular treatment of a MCAD complicated by mesenteric malperfusion following thoracic endovascular aortic repair (TEVAR).…”
Section: Introductionmentioning
confidence: 99%